Synthesis and characterization of diphenylcarbazide-siliceous mesocellular foam and its application as a novel mesoporous sorbent for preconcentration and trace detection of copper and cadmium ions1. Issue 84 (16th September 2015) - Behbahani, Mohammad; Aliakbari, Azam; Amini, Mostafa M.; Behbahani, Ahmad S.; Omidi, Fariborz
<x xml:space="preserve">Abstract</x> We are introducing diphenylcarbazide functionalized siliceous mesocellular foam as a novel mesoporous solid-phase for the extraction of heavy metal ions including copper(ii) and cadmium(ii).